Recurrent Spontaneous Pneumothorax Following Helicopter Travel In High Altitude Areas (Bangladesh Journal of Medical Science, 2013)
A young healthy soldier, non smoker with no previous lung disease, presented with two separate episodes of primary spontaneous pneumothorax within six months, both preceded by low level helicopter travel  during high altitude postings. This diagnosis must be considered in patients with acute onset chest pain and dyspnoea even when other risk factors are seemingly absent. Recurrence is common and so this differential must be kept in mind even after complete treatment of a previous episode.Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 331-333 DOI: http://dx.doi.org/10.3329/bjms.v12i3.12621